Assessing Civic Literacy in Elementary Social Studies amidst the Pandemic - Tyrone Gil; Luis Lorenzo Domingo (Universitas Muhammadiyah Kuningan, 2022)
Assessment in the zenith of the COVID-19 pandemic challenges the teacher’s administration of assessment and evaluation tools to identify learners’ pace in self-learning. This study examined elementary social studies teachers’ assessment tools and practices during the closing of schools and the zenith of distance learning through self-learning modules. Using content analysis, the researchers examined the self-learning modules (SLM), learning packets, and the Most Essential Learning Competencies (MELCs) as the components of the emergency curriculum. The findings exposed the exquisite adaptation of conventional assessment tools among the types of assessment manifested in the SLM. Monitoring and feedbacking, reporting students’ ratings, and authenticity of students’ work were the common problems encountered by teaches. The researchers recommended the utilization of alternative assessment tools to better address the dynamics of civic literacy and flexible appraisal of student achievement. Using technology for assessment will also enhance the delivery of assessment instruction and easiness in validating students’ work.